Measurement of the differential cross section for top quark pair production in pp collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Friedl, M; Frühwirth, R; Ghete, V M; Hartl, C; Hörmann, N; et al. (The European physical journal. C, Particles and fields, 2015)
The normalized differential cross section for top quark pair ([Formula: see text]) production is measured in pp collisions at a centre-of-mass energy of 8[Formula: see text] at the CERN LHC using the CMS detector in data corresponding to an integrated luminosity of 19.7[Formula: see text]. The measurements are performed in the lepton[Formula: see text]jets ([Formula: see text][Formula: see text]jets) and in the dilepton ([Formula: see text], [Formula: see text], and [Formula: see text]) decay channels. The [Formula: see text] cross section is measured as a function of the kinematic properties of the charged leptons, the jets associated to b quarks, the top quarks, and the [Formula: see text] system. The data are compared with several predictions from perturbative quantum chromodynamic up to approximate next-to-next-to-leading-order precision. No significant deviations are observed relative to the standard model predictions.